2022
DOI: 10.1038/s41467-022-29388-0
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of tumor associated macrophages enhances local and systemic platelet-mediated anti-PD-1 delivery for post-surgery tumor recurrence treatment

Abstract: Immunosuppressive cells residing in the tumor microenvironment, especially tumor associated macrophages (TAMs), hinder the infiltration and activation of T cells, limiting the anti-cancer outcomes of immune checkpoint blockade. Here, we report a biocompatible alginate-based hydrogel loaded with Pexidartinib (PLX)-encapsulated nanoparticles that gradually release PLX at the tumor site to block colony-stimulating factor 1 receptors (CSF1R) for depleting TAMs. The controlled TAM depletion creates a favorable mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 56 publications
1
76
0
Order By: Relevance
“…First, we only evaluated the antitumor efficacy of GSC-specific CAR macrophages and microglia on postoperative glioblastoma models. CD133 is also overexpressed in multiple cancers, including lung cancer, liver cancer, and other solid tumors, and the increased density of tumor-associated macrophages has been substantiated to correlate with postsurgery cancer recurrence ( 40 ); thus, it is crucial to further evaluate the antitumor efficacy of our GSC-specific CAR macrophages engineering approach with other tumor models. Second, in our animal studies, we did not observe any detectable toxicity of NP-pCAR, whereas before clinical translation, the long-term safety evaluation should be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…First, we only evaluated the antitumor efficacy of GSC-specific CAR macrophages and microglia on postoperative glioblastoma models. CD133 is also overexpressed in multiple cancers, including lung cancer, liver cancer, and other solid tumors, and the increased density of tumor-associated macrophages has been substantiated to correlate with postsurgery cancer recurrence ( 40 ); thus, it is crucial to further evaluate the antitumor efficacy of our GSC-specific CAR macrophages engineering approach with other tumor models. Second, in our animal studies, we did not observe any detectable toxicity of NP-pCAR, whereas before clinical translation, the long-term safety evaluation should be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…TLR9 agonist lefitolimod in combination with immune checkpoint inhibitor effectively regulates the TME and significantly enhance santitumor effect of anti-PD1/PD-L1 antibodies, which makes lefitolimod an ideal candidate for improving immune checkpoint therapy [ 79 ]. In addition, depletion of TAMs enhances local and systemic platelet-mediated anti-PD-1 delivery for postoperative treatment of tumor recurrence [ 107 ].…”
Section: Tam-associated Therapy In Combination With Other Anticancer ...mentioning
confidence: 99%
“…Leukemia (Kailashiya et al, 2019) Delivering bortezomib Multiple myeloma (Hu et al, 2016) Delivery of lamivudine and tenofovir Viral diseases (Bateman et al, 2016) Encapsulate streptokinase and release Thrombotic disease (Pawlowski et al, 2017) Delivery of aPD-1 antibodies Breast, colon, and melanoma recurrence after surgery (Li et al, 2022) These experimental results revealed that PEVs are highly effective in active targeted therapy. In another study, Li et al developed a platelet-binding αPD-1 antibody for the prognosis of tumor surgery.…”
Section: Carry Doxorubicinmentioning
confidence: 99%